التحديات التي تواجه التربية العملية في جامعة الإمام بن سعود الإسلامية من وجهة نظر الطالبات المعلمات - أبا الخيل، ميمونة بنت صالح (جامعة تبوك, 2023)
هدفت هذه الدراسة إلى التعرف على التحديات التي تواجه الطالبات المعلمات من وجهة نظر الطالبات المعلمات، واستخدمت الاستبانة لجمع المعلومات، وبعد التأكد من صدقها وثباتها، طبقت على (159) طالبة معلمة، حيث تكون مجتمع الدراسة من جميع طالبات التربية العملية بقسم الشريعة، البالغ عددهن (309) طالبات، وكشفت النتائج أن مكتب التربية العملية يقدم ورشة عمل قبل خروج الطالبات المعلمات للتدريب الميداني، وأيضا يوفر دليلا للتربية العملية يقدم لجميع الطالبات المعلمات قبل خروجهن للتدريب الميداني؛ ولكن لا يوجد تناسق بين مكتب التربية العملية والمقررات في الجامعة، وأهم التحديات التي تواجه الطالبات المعلمات المتعلقة بمدارس التدريب هي كثرة عدد الطالبات في الفصل الواحد، وضيق الفصول الدراسية، وتكليف الطالبة المعلمة بعدد أكبر من حصص الاحتياط مقارنة بالمعلمات الأساسيات. وأوصت الدراسة بعدد من التوصيات، منها: *توجيه اهتمام المتخصصين في مجال إعداد المعلم لمعالجة المعوقات التي تعوق تطبيق التربية العملية في المدارس المتعاونة. *إعداد دورات تدريبية وملتقيات للطلاب المعلمين لإعداد الطلبة قبل الخروج للتدريب الميداني في المدارس. This study aimed to identify the challenges facing female student teachers from the female student teacher's point of view. The questionnaire was used to collect information, and after verifying its validity and reliability, it was applied to 159 female student teachers, as the study population consisted of all practical education female students in the Sharia Department, which were (309) female students. The results revealed that the Office of Practical Education has a workshop before the female students leave for field training, and also provides a guide for practical education that is presented to all female student teachers before they leave for field training, but there is no consistency between the Office of Practical Education and the courses at the university, and the most important challenges facing female student teachers are related to training schools is due to the large number of female students in one class, the narrowness of the classes, and the assignment of the student teacher to a larger number of reserve classes compared to the basic teachers. The study recommended a number of recommendations, in- cluding: Directing the attention of specialists in the field of teacher preparation to address the obstacles that hinder the application of practical education in cooperating schools. Preparing training courses and forums for student teachers to prepare students before going out for field training in schools.
Keywords: طلبة الجامعات -- المقررات الجامعية -- المملكة العربية السعودية